SOLASI CENDAWAN ENTOMOPATOGEN PADA SERANGGA TERINFEKSI DI DAERAH PERTANIAN KECAMATAN X KOTO TANAH DATAR - Hidayat, Yosmed (Sainstek : Jurnal Sains dan Teknologi, 2010)
Operation of pesticide population require to be conducted. This time operation which conducted many is chemically, which can leave dangerous residu to environment. In this time have been developed by method operation of white pest by exploiting mushroom of entomopatogen which is have potency to as agent involve for the controller of pest. For that have been conducted by research with aim to in searching, insulation, and identify various mushroom type of entomopatogen which is insulation at infection insect around area agriculture of kecamatan  X Koto Tanah Datar. Identify through perception of characteristic of makroskopis and is microscopic of mushroom which is insulation. Result of research indicate that from four insulation area found by 12 mushroom type of entomopatogen (Sp.1, Sp.2, A. niger, Aspergillus sp.1, Aspergillus sp.2, Aspergillus sp.3, Aspergillus sp.4, Aspergillus sp.5, Penicillium sp.1, Penicillium sp.2, Penicillium sp.3, Penicillium sp.4.Key words: entomopatogen, aspergillus, penicillium